The usefulness of a dermocosmetic containing Myrtus communis extract and azelaic acid for maintenance phase of adult female acne: Results from a randomized exploratory investigator-blinded comparative study - Bagatin, Edileia; Thouvenin, Marie Dominique; Bacquey, Adeline; Baradat, Sophie; Lauze, Christophe; Mengeaud, Valerie; Soares, Juliana L. M.; Andrade, Leonardo de S.M.; Miot, Helio A. [UNESP]; Rocha, Marco Alexandre (My University, 2023)
Background: Acne is a very common condition. Currently, there are relatively few studies available to help guidance-based decisions for its long-term management, especially studies with cosmetic care products. We have developed a skin care product dedicated to adult female acne. Objectives: Evaluate the efficacy and tolerance of the test product containing Myrtus communis extract and azelaic acid compared with a light moisturizing cream (LCM) in adult females in the acne maintenance phase. Methods: A clinical study was conducted as a Brazilian, multicentre, randomized, investigator-blinded trial in adult females with clear or almost clear facial acne after anti-acne treatment. The test group (26 subjects) applied the test product and the comparative product group (27 subjects) applied LCM. Both groups applied the products twice daily on the whole face. Subjects were evaluated every 4 weeks over 16 weeks. Efficacy was evaluated according to acne relapse; Investigator's Global Assessment (IGA); acne lesions counting; AcneQoL questionnaire; Subject Global change Assessment (SGA) of acne severity; and the number of Post-Inflammatory Hyperpigmentation (PIH) and Post-Inflammatory Erythema (PIE) lesions. Tolerance was assessed according to a 5-point scale. Results: Over 16 weeks, the number of acne relapse was more than double in the comparator compared to the test product group (eight subjects vs. three subjects respectively). There was no statistical difference in the evolution of the mean IGA from baseline between the two groups; however, 85% of subjects were assessed as clear or almost clear in the test product group and 67% in the comparative group. Conclusions: This study demonstrated the effectiveness topical application of the test product compared to LCM on acne severity in the maintenance phase of adult female acne. Efficacy results after 16 weeks suggested a trend to limit acne relapses and a benefit of the test product in maintaining long-term remission.